Trickier Trace

Algebra Level 5

For any positive integer n n , the n × n n \times n matrix A ( n ) A(n) has components A ( n ) u , v = 1 min ( u , v ) 1 u , v n A(n)_{u,v} \; = \; \frac{1}{\min(u,v)} \hspace{2cm} 1 \le u,v \le n Define the quantity X ( n ) X(n) by the formula X ( n ) = T r [ A ( n ) 2 ] + 4 T r [ A ( n ) 1 ] + ( n 2 ) ( n 1 ) n ( n + 1 ) 1 n 1 X(n) \; = \; \mathrm{Tr}\big[A(n)^{-2}\big] + 4\,\mathrm{Tr}\big[A(n)^{-1}\big] + (n-2)(n-1)n(n+1) - 1 \hspace{2cm} n \ge 1 where T r B \mathrm{Tr\,B} denotes the trace of the matrix B B . It can be shown that the infinite sum n = 3 X ( n ) 1 \sum_{n=3}^\infty X(n)^{-1} converges to the rational limit A B \frac{A}{B} where A , B A,B are coprime positive integers. Find the value of A + B A + B .

Inspiration


The answer is 581.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jun 22, 2020

Let F n ( t ) F_n(t) be the characteristic polynomial of A ( n ) A(n) . In the first round of this question, I showed that F n ( t ) = ( t + 1 n ( n 1 ) ) F n 1 ( t ) + t d e t B n 1 ( t ) n 3 F_n(t) \; = \; \left(t + \tfrac{1}{n(n-1)}\right)F_{n-1}(t) + t\,\mathrm{det} B_{n-1}(t) \hspace{2cm} n \ge 3 where B n 1 ( t ) B_{n-1}(t) is the ( n 1 ) × ( n 1 ) (n-1)\times(n-1) matrix that only differs from t I n 1 A n 1 t I_{n-1} - A_{n-1} by having 1 n 1 -\tfrac{1}{n-1} , instead of t 1 n 1 t-\tfrac{1}{n-1} , in the bottom right corner. This, together with the initial values F 1 ( t ) = t 1 F_1(t) = t-1 , F 2 ( t ) = t 2 3 2 t 1 2 F_2(t) = t^2 - \tfrac32t -\tfrac12 implied that n ! ( n 1 ) ! F n ( 0 ) = 1 T r [ A ( n ) 1 ] = n ! ( n 1 ) ! F n ( 0 ) = 1 2 3 ( n 1 ) n ( n + 1 ) n 1 n!(n-1)! F_n(0) \; = \; -1 \hspace{1cm} \mathrm{Tr}\big[A(n)^{-1}\big] \; = \; n!(n-1)!F_n'(0) \; = \; 1 - \tfrac23(n-1)n(n+1) \hspace{2cm} n \ge 1 Following these ideas further, the fact that the determinant or a matrix is a multilinear function of its rows means that d e t B n 1 ( t ) = 1 1 2 t I n 2 A ( n 2 ) 1 n 2 1 1 2 1 n 2 1 n 1 = 1 1 2 t I n 2 A ( n 2 ) 1 n 2 1 1 2 1 n 2 t 1 n 1 1 1 2 t I n 2 A ( n 2 ) 1 n 2 0 0 0 t = F n 1 ( t ) t F n 2 ( t ) \begin{aligned} \mathrm{det}\,B_{n-1}(t) & = \; \left| \begin{array}{ccccc|c} & & & & & -1 \\ & & & & & -\frac12 \\ & & tI_{n-2} - A(n-2) & & & \vdots \\ & & & & & \vdots \\ & & & & & -\frac{1}{n-2} \\ \hline -1 & -\frac12 & \cdots & & -\frac{1}{n-2} & -\frac{1}{n-1} \end{array} \right| \\[4ex] & = \;\left| \begin{array}{ccccc|c} & & & & & -1 \\ & & & & & -\frac12 \\ & & tI_{n-2} - A(n-2) & & & \vdots \\ & & & & & \vdots \\ & & & & & -\frac{1}{n-2} \\ \hline -1 & -\frac12 & \cdots & & -\frac{1}{n-2} & t-\frac{1}{n-1} \end{array} \right| - \left| \begin{array}{ccccc|c} & & & & & -1 \\ & & & & & -\frac12 \\ & & tI_{n-2} - A(n-2) & & & \vdots \\ & & & & & \vdots \\ & & & & & -\frac{1}{n-2} \\ \hline 0 & 0 & \cdots & & 0 & t \end{array} \right| \\[4ex] & = \; F_{n-1}(t) - tF_{n-2}(t) \end{aligned} for n 3 n \ge 3 , so we deduce that F n ( t ) = ( 2 t + 1 n ( n 1 ) ) F n 1 ( t ) t 2 F n 2 ( t ) n 3 F_n(t) \; = \; \left(2t + \tfrac{1}{n(n-1)}\right)F_{n-1}(t) - t^2F_{n-2}(t) \hspace{2cm} n \ge 3 and hence that F n ( 0 ) = 1 n ( n 1 ) F n 1 ( 0 ) + 4 F n 1 ( 0 ) 2 F n 2 ( 0 ) n 3 F_n''(0) \; = \; \tfrac{1}{n(n-1)}F_{n-1}''(0) + 4F_{n-1}'(0) -2F_{n-2}(0) \hspace{2cm} n \ge 3 This implies that n ! ( n 1 ) ! F n ( 0 ) = ( n 1 ) ! ( n 2 ) ! F n 1 ( 0 ) + 4 n ! ( n 1 ) ! F n 1 ( 0 ) 2 n ! ( n 1 ) ! F n 2 ( 0 ) = ( n 1 ) ! ( n 2 ) ! F n 1 ( 0 ) + 4 n ( n 1 ) [ 1 2 3 ( n 2 ) ( n 1 ) n ] + 2 n ( n 1 ) 2 ( n 2 ) = ( n 1 ) ! ( n 2 ) ! F n 1 ( 0 ) 2 3 n ( n 1 ) [ 4 n 3 15 n 2 + 17 n 12 ] \begin{aligned} n! (n-1)! F_n''(0) & = \; (n-1)!(n-2)!F_{n-1}''(0) + 4n!(n-1)!F_{n-1}'(0) - 2n!(n-1)!F_{n-2}(0) \\ & = \; (n-1)!(n-2)!F_{n-1}''(0) + 4n(n-1)\left[1 - \tfrac23(n-2)(n-1)n\right] + 2n(n-1)^2(n-2) \\ & = \; (n-1)!(n-2)!F_{n-1}''(0) - \tfrac23n(n-1)\big[4n^3 - 15n^2 + 17n - 12\big] \end{aligned} for n 3 n \ge 3 , and hence n ! ( n 1 ) ! F n ( 0 ) = 4 2 3 r = 3 n r ( r 1 ) [ 4 r 3 15 r 2 + 17 r 12 ] = 4 9 n 6 + 6 5 n 5 1 9 n 4 + 5 9 n 2 6 5 n 4 n 2 n!(n-1)! F_n''(0) \; = \; 4 -\tfrac23\sum_{r=3}^n r(r-1)\big[4r^3 - 15r^2 + 17r - 12\big] \; = \; -\tfrac49n^6 + \tfrac65n^5 - \tfrac19n^4 + \tfrac59n^2 - \tfrac65n - 4 \hspace{1.5cm} n \ge 2 Using Vieta's formulae, if u n 1 , u n 2 , , u n n u_{n1},u_{n2}, \ldots,u_{nn} are the eigenvalues of A ( n ) A(n) , then T r [ A ( n ) 1 ] = j u n j 1 = F n ( 0 ) F n ( 0 ) = 1 2 3 ( n 1 ) n ( n + 1 ) j < k u n j 1 u n k 1 = F n ( 0 ) 2 F n ( 0 ) = 2 9 n 6 3 5 n 5 + 1 18 n 4 5 18 n 2 + 3 5 n + 2 \begin{aligned} \mathrm{Tr}\big[A(n)^{-1}\big] \; = \; \sum_{j} u_{nj}^{-1} & = \; -\frac{F_n'(0)}{F_n(0)} \; = \; 1 - \tfrac23(n-1)n(n+1) \\ \sum_{j<k} u_{nj}^{-1}u_{nk}^{-1} & = \; \frac{F_n''(0)}{2 F_n(0)} \; = \; \tfrac29n^6 - \tfrac35n^5 + \tfrac{1}{18}n^4 - \tfrac{5}{18}n^2 + \tfrac35n + 2 \end{aligned} for n 2 n \ge 2 , from which we deduce that T r [ A ( n ) 2 ] = j u n j 2 = ( j u n j 1 ) 2 2 j < k u n j 1 u n k 1 = 1 15 ( n 1 ) n ( n + 1 ) ( 18 n 2 15 n 2 ) 3 \mathrm{Tr}\big[A(n)^{-2}\big] \; = \; \sum_j u_{nj}^{-2} \; = \;\left(\sum_ju_{nj}^{-1}\right)^2 - 2\sum_{j<k}u_{nj}^{-1}u_{nk}^{-1} \; = \; \tfrac{1}{15}(n-1)n(n+1)(18n^2 - 15n - 2) - 3 for all n 2 n \ge 2 . But then we deduce that X ( n ) = { 6 5 ( n 2 ) ( n 1 ) n ( n + 1 ) ( n + 2 ) n 2 4 n = 1 X(n) \; = \; \left\{ \begin{array}{lll} \tfrac65(n-2)(n-1)n(n+1)(n+2) & \hspace{1cm}& n \ge 2 \\[2ex] 4 & & n = 1 \end{array}\right. and hence we deduce that n = 3 X ( n ) 1 = 5 24 n = 3 ( 1 ( n 2 ) ( n 1 ) n ( n + 1 ) 1 ( n 1 ) n ( n + 1 ) ( n + 2 ) ) = 5 576 \sum_{n=3}^\infty X(n)^{-1} \; = \; \frac{5}{24}\sum_{n=3}^\infty \left(\frac{1}{(n-2)(n-1)n(n+1)} - \frac{1}{(n-1)n(n+1)(n+2)}\right) \; = \; \frac{5}{576} making the answer 5 + 576 = 581 5 + 576 = \boxed{581} .


Just as there was an alternate approach to the first part of this question, there is an alternate approach to the second part. Recall that

A ( n + 1 ) 1 = ( 0 0 A ( n ) 1 n ( n + 1 ) K ( n ) 0 n ( n + 1 ) 0 0 0 n ( n + 1 ) n ( n + 1 ) ) A(n+1)^{-1} \; = \; \left(\begin{array}{ccccc|c} & & & & & 0 \\ & & & & & 0 \\ & & A(n)^{-1} - n(n+1)K(n) & & & \vdots \\ & & & & & 0 \\ & & & & & n(n+1) \\\hline 0 & 0 & \cdots & 0 & n(n+1) & -n(n+1) \end{array}\right) where K ( n ) K(n) is the n × n n \times n matrix with zeros in all components except the bottom right one, which has the value 1 1 . This implies that A ( n + 1 ) 2 = ( ( A ( n ) 1 n ( n + 1 ) K ( n ) ) 2 + n 2 ( n + 1 ) 2 K ( n ) 2 n 2 ( n + 1 ) 2 ) A(n+1)^{-2} \; = \; \left(\begin{array}{ccccc|c} & & & & & \star \\ & & & & & \star \\ & & \big(A(n)^{-1} - n(n+1)K(n)\big)^2 & & & \vdots \\ & & + n^2(n+1)^2K(n)& & & \star \\ & & & & & \star \\\hline \star & \star & \cdots & \star & \star & 2n^2(n+1)^2 \end{array}\right) where the stars indicate that the values in those places are unimportant. Thus T r [ A ( n + 1 ) 2 ] = T r [ ( A ( n ) 1 n ( n + 1 ) K ( n ) ) 2 ] + 3 n 2 ( n + 1 ) 2 = T r [ A ( n ) 2 ] 2 n ( n + 1 ) T r [ K ( n ) A ( n ) 1 ] + 4 n 2 ( n + 1 ) 2 \mathrm{Tr}\big[A(n+1)^{-2}\big] \; = \; \mathrm{Tr}\big[\big(A(n)^{-1} - n(n+1)K(n)\big)^2\big] + 3n^2(n+1)^2 \; = \; \mathrm{Tr}\big[A(n)^{-2}\big] - 2n(n+1)\,\mathrm{Tr}\big[K(n)A(n)^{-1}] + 4n^2(n+1)^2

It is easy to calculate that T r [ K ( n + 1 ) A ( n + 1 ) 1 ] = n ( n + 1 ) \mathrm{Tr}\big[K(n+1)A(n+1)^{-1}\big] = -n(n+1) for all n 1 n \ge 1 , and hence T r [ A ( n + 1 ) 1 ] = T r [ A ( n ) 2 ] + 2 ( n + 1 ) n 2 ( n 1 ) + 4 n 2 ( n + 1 ) 2 = T r [ A ( n ) 2 ] + 2 n 2 ( n + 1 ) ( 3 n + 1 ) \mathrm{Tr}\big[A(n+1)^{-1}\big] \; = \; \mathrm{Tr}\big[A(n)^{-2}\big] + 2(n+1)n^2(n-1) + 4n^2(n+1)^2 \; = \; \mathrm{Tr}\big[A(n)^{-2}\big] + 2n^2(n+1)(3n+1) for all n 2 n \ge 2 , and hence T r [ A ( n ) 2 ] = 13 + 2 r = 2 n 1 r 2 ( r + 1 ) ( 3 r + 1 ) = 1 15 ( n 1 ) n ( n + 1 ) ( 18 n 2 15 n 2 ) 3 \mathrm{Tr}\big[A(n)^{-2}\big] \; =\; 13 + 2\sum_{r=2}^{n-1}r^2(r+1)(3r+1) \; = \; \tfrac{1}{15}(n-1)n(n+1)(18n^2 - 15n - 2) - 3 for n 2 n \ge 2 , as before.


Simplest yet, the above observations about the matrix A ( n ) A(n) make it easy to show that the inverse of A ( n ) A(n) is the symmetric tridiagonal matrix A ( n ) 1 = ( a 1 b 1 0 0 0 0 b 1 a 2 b 2 0 0 0 0 b 2 a 3 b 3 0 0 0 0 b 3 a 4 0 0 0 0 0 0 a n 1 b n 1 0 0 0 0 b n 1 a n ) A(n)^{-1} \; = \; \left(\begin{array}{ccccccc} a_1 & b_1 & 0 & 0 & \cdots & 0 & 0 \\ b_1 & a_2 & b_2 & 0 & \cdots & 0 & 0 \\ 0 & b_2 & a_3 & b_3 & \cdots & 0 & 0 \\ 0 & 0 & b_3 & a_4 & \cdots & 0 & 0 \\ \vdots & \vdots & \vdots & \vdots & \ddots & \vdots & \vdots \\ 0 & 0 & 0 & 0 & \cdots & a_{n-1} & b_{n-1} \\ 0 & 0 & 0 & 0 & \cdots & b_{n-1} & a_n \end{array} \right) where a j = { 1 j = 1 2 j 2 2 j n 1 n ( n 1 ) j = n b j = j ( j + 1 ) 1 j n 1 a_j \; = \; \left\{ \begin{array}{lll} -1 & \hspace{1cm} & j = 1 \\ -2j^2 & & 2 \le j \le n-1 \\ -n(n-1) & & j = n \end{array}\right. \hspace{2.5cm} b_j \; = \; j(j+1) \hspace{1cm} 1 \le j \le n-1 and hence we can just calculate T r [ A ( n ) 1 ] = j = 1 n a j T r [ A ( n ) 2 ] = j = 1 n a j 2 + 2 j = 1 n 1 b j 2 \mathrm{Tr}\big[A(n)^{-1}\big] \; = \; \sum_{j=1}^n a_j \hspace{2cm} \mathrm{Tr}\big[A(n)^{-2}\big] \; = \; \sum_{j=1}^n a_j^2 + 2\sum_{j=1}^{n-1}b_j^2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...